Penerapan Disiplin Pegawai Pemerintah Dengan Perjanjian Kerja (PPPK) Menurut Peraturan Pemerintah Nomor 49 Tahun 2018 dan Fiqih Siyasah - Al Fikri, Muhamad Mufid; Rohmah, Siti Ngainnur; Sajali, Munawir (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Government Employees with Employment Agreements (PPPK) are required to comply with regulations relating to employment and are required to have good behavior such as being loyal and obedient to the stateIn siyasa fiqh it is referred to as tabi'in (followers). Where tabi'in are required to obey and obey the orders and rules made by ulil amri (Leader). The purpose of this study is to find out the application of government employee discipline with work agreements (PPPK) according to PP no. 49 of 2018 concerning Management of Government Employees with Work Agreements (PPPK). Knowing the Application of Discipline for Government Employees with Employment Agreements (PPPK) According to Fiqh Siyasah. The results of the study show that the application of disciplinary regulations for Government Employees with Employment Agreements (PPPK) is confirmed in Government Regulation No. 49 of 2018 article 51 and article 52 but in these articles, it is explained that the imposition of disciplinary sanctions is carried out by government agencies that have the authority to impose sanctions on employees. In adhering to the Siyasah Fiqh principles in the application of employee discipline, employees must have the principles of sovereignty, the principles of justice, the principles of deliberation and Ijma', the principles of equality, the principles of the obligations of the state and the people and the principle of amar ma'ruf nahi munkar. Keywords: Work Discipline; PPPK; Fiqh Siyasah Abstrak Pegawai Pemerintah Dengan Perjanjian Kerja (PPPK) wajib mematuhi peraturan-peraturan yang berkaitan dengan kepegawaian dan wajib berkelakuan baik seperti setia dan taat kepada negara. Dalam fiqh siyasah disebut sebagai tabi’in (pengikut). Dimana tabi’in diwajibkan untuk patuh dan taat terhadap perintah dan aturan yang dibuat oleh ulil amri (Pemimpin). Tujuan dari penelitian ini adalah Untuk Mengetahui Penerapan Disiplin Pegawai Pemerintah Dengan Perjanjian Kerja (PPPK) Menurut PP No. 49 Tahun 2018 tentang Manajemen Pegawai Pemerintah dengan Perjanjian Kerja (PPPK). Mengetahui Penerapan Disiplin Pegawai Pemerintah Dengan Perjanjian Kerja (PPPK) Menurut Fiqih Siyasah. Hasil penelitian menunjukkan bahwa Penerapan peraturan disiplin bagi Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) ditegaskan pada Peraturan Pemerintah No. 49 Tahun 2018 pasal 51 maupun pasal 52 namun didalam pasal tersebut dijelaskan bahwa pemberian sanksi disiplin dilakukan oleh instansi pemerintah yang memiliki kewenangan untuk memberikan sanksi kepada Pegawai Pemerintah. Dalam menegakan prinsip Fiqih Siyasah pada penerapan disiplin pegawai harus memiliki prinsip kedaulatan, prinsip keadilan, prinsip musyawarah dan Ijma’, prinsip persamaan, prinsip hak kewajiban negara dan rakyat serta prinsip amar ma’ruf nahi munkar. Kata Kunci: Disiplin Kerja; PPPK; Fiqih Siyasah